2002
DOI: 10.1111/1467-8624.00487
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and Construct Validation of the Big Five Factors in Early Childhood: A Longitudinal Analysis of Their Ontogeny in Sweden

Abstract: Researchers have shown that the five major dimensions of personality (extraversion, agreeableness, conscientiousness, neuroticism, and openness to experience) and two additional factors (irritability and positive activity) are evident from adolescence. This study attempted to replicate and extend these results in a longitudinal study of 102 Swedish children, followed from 2.3 to 15.2 years of age. Item analyses revealed consistently reliable irritability, conscientiousness, and positive activity factors, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
120
3
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(141 citation statements)
references
References 29 publications
13
120
3
5
Order By: Relevance
“…Clearly, the 18-item set currently comprising the Openness scale lacks coherence and homogeneity. Low internal consistency for the Openness factor has also been reported by other researchers using different methods of measuring the Big 5 (Caspi & Shiner, 2006;Lamb, Chuang, Wessels, Broberg, & Hwang, 1996). On a conceptual level, most people would accept the proposition that young children do exhibit variation in a trait parallel to Openness in adults; for example, curiosity and exploratory behaviour are well-researched patterns in this age group.…”
Section: Discussionmentioning
confidence: 78%
“…Clearly, the 18-item set currently comprising the Openness scale lacks coherence and homogeneity. Low internal consistency for the Openness factor has also been reported by other researchers using different methods of measuring the Big 5 (Caspi & Shiner, 2006;Lamb, Chuang, Wessels, Broberg, & Hwang, 1996). On a conceptual level, most people would accept the proposition that young children do exhibit variation in a trait parallel to Openness in adults; for example, curiosity and exploratory behaviour are well-researched patterns in this age group.…”
Section: Discussionmentioning
confidence: 78%
“…On the one hand, some researchers have moved toward accepting the Big Five as a representation of basic personality trait dimensions in childhood and adolescence (e.g., Digman, 1994;Goldberg, 2001;Halverson et al, 2003;Kohnstamm, Halverson, Mervielde, & Havill, 1998). On the other hand, several findings are not easily reconciled with the canonical Big Five structure (e.g., Hampson & Goldberg, 2006;John, Caspi, Robins, Moffitt, & Stouthamer-Loeber, 1994;Lamb, Chuang, Wessels, Broberg, & Hwang, 2002;van Lieshout & Haselager, 1994), and further research is needed before the issue can be considered settled.…”
Section: Changes In Basic Personality Trait Structurementioning
confidence: 99%
“…To date, several independent research groups traced five-factor-like dimensions in adolescents and children by adopting a variety of strategies, informants, and methods of assessment [for an overview; 6] and demonstrated that these variables are meaningfully linked to the five dimensions established in adults [54]. Recent studies have retrieved these five personality factors from adult ratings of children as young as age 2 [55], age 3-4 [e.g., 56,57], and even from self-reports of children aged 5 [58].…”
Section: Capturing the Common Tenets Of Temperamentmentioning
confidence: 99%